2005
DOI: 10.1620/tjem.206.7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tirofiban and Clopidogrel Pretreatment on Outcome of Old Saphenous Vein Graft Stenting in Patients with Acute Coronary Syndromes

Abstract: In spite of developments in interventional cardiology, the success rate of saphenous vein graft stenting is still low in patients with acute coronary syndromes. In this study, we aimed at finding out the effect of pretreatment with Tirofiban, a glycoprotein IIb/IIIa inhibitor, and clopidogrel, an adenosine diphosphate antagonist, on the outcome of saphenous vein graft stenting in patients with acute coronary syndrome. A total of 47 patients, who had lesions in saphenous vein grafts and acute coronary syndrome,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Ozkan et al have suggested that a combination of clopidogrel with glycoprotein IIb‐IIIa inhibitors could offer additional benefits in patients with acute coronary syndrome due to culprit lesions in SVGs especially in diabetic patients. In their 47‐patient study, subjects who were pretreated with tirofiban and clopidogrel for 48 h before the intervention had a significant lower rate of no‐reflow or slow‐reflow phenomenon compared to the untreated group (1 patient vs. 9 patients, P = 0.004).…”
Section: Introductionmentioning
confidence: 99%
“…Ozkan et al have suggested that a combination of clopidogrel with glycoprotein IIb‐IIIa inhibitors could offer additional benefits in patients with acute coronary syndrome due to culprit lesions in SVGs especially in diabetic patients. In their 47‐patient study, subjects who were pretreated with tirofiban and clopidogrel for 48 h before the intervention had a significant lower rate of no‐reflow or slow‐reflow phenomenon compared to the untreated group (1 patient vs. 9 patients, P = 0.004).…”
Section: Introductionmentioning
confidence: 99%